Adapted physical activity in subjects and athletes recovering from COVID-19: a position statement of the Società Italiana Scienze Motorie e Sportive - Venturelli, M.; Mancini, A.; Di Cagno, A.; Fiorilli, G.; Paneroni, M.; Roggio, F.; Musumeci, G.; Buono, P.; Schena, F.; Paoli, A. (Sport Sciences for Health, 2022)
Coronavirus disease 2019 (COVID-19) is a worldwide pandemic illness that is impacting the cardiovascular, pulmonary, musculoskeletal, and cognitive function of a large spectrum of the worldwide population. The available pharmacological countermeasures of these long-term effects of COVID-19 are minimal, while myriads of non-specific non-pharmacological treatments are emerging in the literature. In this complicated scenario, particular emphasis should be dedicated to specific exercise interventions tailored for subjects and athletes recovering from COVID-19. Specific guidelines on adapted physical activity in this critical population are unavailable so far, therefore, in this position statement of the Società Italiana di Scienze Motorie e Sportive (SISMeS) the members of the steering committee of the research group Attività Motoria Adattata, Alimentazione, Salute e Fitness have indicated the adapted physical activity approaches to counteract the long-term effects of the COVID-19, both in good health people and athletes.